Os olhos ubíquos do espelho: um estudo das percepções de civilidade na obra “A Civilidade Pueril” (1530), de Erasmo de Rotterdam - Pisani, Ana Luisa (2016)
The present Dissertation presents a study of the civility discourse in “De civilitate morum puerilium” (1530), Erasmus of Rotterdam (1466-1536), and its implications in the compiling context and diffusion of this manual. By the addition of new themes in the history field, this works performs reflections regarding the social, religious and politic aspects of the manners suggested by Erasmus. In this way, it is analysed the continuous process of recriation of body signs and their respective symbolic construction of meanings in the 16th century. By these aspects, it is discussed how the new ways of knowledge, under the Christian and humanistic points of view, besides its own communication, impact the social life spreading and reinforce a real control of the bodies, from a vigilance which imposes itself more and more present and constant by the “ubiquitous eyes”. These “eyes” promote new sensitiveness, such as embarrassment, shame, pride and the own distinction, as a consequence of the paradigm about the ideal appearance and, therefore, desired